A look at Graves’ hyperthyroidism in pregnancy - Nguyen, Caroline T.; Mestman, Jorge H. (Annals of Thyroid; Vol 3 (November 2018): Annals of Thyroid, 2018)
Maternal, obstetrical, and neonatal complications are increased in women with poorly controlled thyroid disease during pregnancy. Establishing the correct diagnosis and effectively managing Graves’ hyperthyroidism (GH) remains challenging for physicians due to several reasons including, but not limited to changes in thyroid physiology during pregnancy, effect of pregnancy on laboratory testing, and teratogenicity associated with anti-thyroid drugs. This paper will review the diagnosis and management of GH in pregnancy and address: (I) preconception counseling; (II) alterations in thyroid physiology in pregnancy; (III) thyroid laboratory testing; (IV) etiologies of hyperthyroidism; (V) pregnancy-related complications; (VI) maternal management; (VII) neonatal management; (VIII) ATDs and the associated maternal and fetal complications; and (IX) post-partum management. Establishing the diagnosis of GH early, maintaining euthyroidism throughout the duration of pregnancy, and avoiding overtreatment of the fetus with antithyroid drugs (ATDs) is essential to reducing the risk of complications for the mother, fetus, and newborn. The successful care of these complex patients requires close collaboration between the endocrinologist, maternal-fetal-medicine specialist, obstetrician, neonatologist, and pediatric endocrinologist.